(untitled) (Journal of Advanced Research in Social Sciences, 2019)
Based on component of poverty line of Bangka Belitung Islands, percentage of cigarette consumption expenditures was the second largest for the poverty line, while rice as staple food only occupies the fourth position. Cigarettes do not contain calories, so they will not add calories by consuming them. It is possible for someone who has an expenditure above the poverty line to remain poor because many are spent for consuming cigarettes. The purpose of the study to analyze the impact of cigarette consumption on poverty status, with a simulation converting cigarette expenditure into spending on other foods containing calories. In particular, to study whether there is a change in poverty status after conversion of cigarette expenditure. And analyzing the influence of social, economic and demographic characteristics on changes in poverty status. The study focused on poor households that have cigarette expenditure. This study uses data of 7080 households from all regencies and cities in Bangka Belitung province, which collected from the field study by students of Polytechnic of Statistics STIS in 2017. The simulation results show that there is a significant change in poverty status when converting cigarette expenditure. And based on binary logistic regression analysis the results show that households with a higher level of education, status of head of household as employee or having a business, non-agricultural employment and an increase in per capita income have a greater tendency to change the poverty status of households. Thus, cigarette expenditure can change poverty status if it can be used for better needs.